Optimizing Budgeting and Financial Management for Sustainable Economic Growth and Fiscal Resilience - Cherniaieva, Olena; Mуkhalchenko, Hanna; Ataieva, Olena; Marshalok, Taras; Petrukha, Serhii (European Journal of Sustainable Development, 2025)
Efficient macro-level budgeting serves as a fundamental instrument for overseeing a nation's economy, fostering sustainable growth and advancing social progress. Fiscal policy plays a crucial role in ensuring the state's financial support for socio-economic development, and its improvement is a priority task for ensuring stability and sustainable development. The purpose of this study is to analyze the effectiveness of budgeting and financial management mechanisms, as well as to develop ways to optimize them to ensure sustainable development. To achieve this goal, various scientific methods were used, including a monographic approach, statistical analysis, the method of expert assessments, and mathematical and statistical modeling. The study defines the theoretical foundations of the budget process, outlines the stages and conditions of its implementation, and analyzes the current challenges of budgeting in the economic and social contexts. The structure, algorithms, and main components of the budgeting system are studied, and the effectiveness of its implementation as a component of financial management is evaluated. The key factors affecting the effectiveness of the budgeting process are identified and the necessity of its optimization to increase the strategic sustainability of public finances is substantiated. The article substantiates the conceptual foundations of applying the budgeting methodology for effective financial management, suggests directions for improving the mechanisms of formation and distribution of budgetary resources, and identifies appropriate tools for implementing these measures. The practical significance of the obtained results lies in their applicability to real processes of optimization of financial management technologies, which will help to increase the efficiency of the state financial policy and ensure sustainable development. Keywords: financial planning, strategy, financial management, economic effect,budget optimization taxes.